Decentralization of Islamic Education Governance in Indonesia: Power Relationships and Madrasah Autonomy - Agus Irfan; Purwita Kusumaning Tias (Universitas Islam Sultan Agung, 2026)
The decentralization of government in Indonesia, which began in 2001, has brought about significant transformations in public governance. However, these transformations have not yet fully extended to Islamic education. This article analyzes the paradox of decentralization in madrasah governance: on the one hand, regional autonomy creates space for diversity in educational management, but on the other hand, madrasahs remain bound to centralized bureaucratic control through the Ministry of Religious Affairs. Using a socio-legal approach and the theory of power relations in governance, this article examines how four key actors—the central government, the Ministry of Religious Affairs, local governments, and madrasahs—interact in the struggle for authority over Islamic education. Data from the Ministry of Religious Affairs’ EMIS (for the 2022/2023 academic year) shows that of the 55,535 registered madrasahs at the MI, MTs, and MA levels, 92.7 percent (51,507 units) are private and rely on community resources, while only 7.3 percent (4,046 schools) are public and receive direct funding from the state. Governance disparities between madrasahs in Java and outside Java, as well as between urban areas and underdeveloped, remote, and outermost (3T) regions, reflect the challenges of decentralization in fairly distributing capacity and resources. This article argues that a co-governance model involving active collaboration between the Ministry of Religious Affairs, local governments, and the madrasah community is a strategic alternative for achieving more meaningful autonomy in Islamic education.